Angiogenesis Revisited: An Overlooked Role of Endothelial Cell Metabolism in Vessel Sprouting. (October 2015) - Vandekeere, Saar; Dewerchin, Mieke; Carmeliet, Peter
Abstract During vessel sprouting, endothelial "tip" cells migrate at the forefront, while the endothelial "stalk" cells elongate the sprout; endothelial "phalanx" cells line quiescent vessels. Tip and stalk cells can dynamically switch phenotypes under the control of VEGF and Notch signaling. Novel findings now show that in addition to signaling cascades, metabolism coregulates the formation of the new vasculature. Recent studies demonstrated that ECs rely primarily on glycolysis for ATP production, that glycolysis is further enhanced in angiogenic ECs, and that the key glycolytic regulator PFKFB3 codetermines angiogenesis by controlling the balance of tip versus stalk cells and promoting a migratory tip cell phenotype. On the other hand, FAO regulates endothelial stalk cell proliferation by providing carbon sources for biosynthetic processes, more particularly for de novo nucleotide synthesis for DNA replication. Here, we overview the current understanding of the various metabolic pathways in ECs and their impact on vessel formation in health and disease.